PENGARUH RASIO KEUANGAN TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI ERA 4.0 - Nissa Amrina *; Reny Fitriana Kaban (Perbanas Journal of Islamic Economics and Business, 2021)
The world today has entered the era of the industrial revolution 4.0, where this era greatly affects the various lifestyles of people around the world, including in Indonesia. One of the industries moving by 4.0 is the Islamic banking industry. The impact of using this technology should make Islamic banking operations more efficient, so that the profitability of Islamic banking in Indonesia will also increase. This study was conducted with the aim of looking at the profitability of Islamic commercial banks in Indonesia in the era of the industrial revolution 4.0 from 2013 to 2019. The population in this study was Islamic Commercial Banks registered by the Otoritas Jasa Keuangan in the period 2013-2019 with a sample of 11 Islamic Commercial Banks that corresponding. This research is a quantitative research with the data collection method used is documentation (library research), which uses bank financial reports published by the Otoritas Jasa Keuangan (OJK) as of December 31, 2013 to 2019. The variables used in this study consisted of CAR, NPF, NIM and BOPO. The results of this study indicate that the CAR and BOPO variables have an effect on ROA. While the NPF and NIM variables have no effect on ROA. Based on the results of the value of 82.48% of the coefficient of determination (R²) also shows that all the variables tested together are able to explain the effect that occurs on the ROA variable. The results of this study are expected to be a reference for Islamic banks according to business activities in Indonesia in an effort to improve operational efficiency so as to improve their performance and profitability.